1 3 3

: 1

  1. #1

    Jul 2012
    5,281

    1

    : -
    1- ( 1 , 3 ) ( 4 , 4 ) , ( - 2 , 2 ) , ( 2 , 6 )
    :-

    :
    = ( ( 2 - 1 )^2 + ( 2 - 1 )^2 )
    = (( 4 - 1 )^2 + ( 4 - 3 )^2 )= ( 10 )

    = ( ( - 2 - 1 )^2 + ( 2 - 3 )^2 ) = ( 10 )

    ( ( 2 - 1 )^2 + ( 6 - 3 )^2 ) = ( 10 )
    ( 1 , 3 )


    :-



    ( 0 , - 5 ) , ( - 9 , 7 ) , ( 16 , 7 )

    :-





    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( - 9 - 0 )^2 + ( 7 + 5 )^2 ) = ( 81 + 144 ) = ( 225 ) = 15

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( 16 - 0 )^2 + ( 7 + 5 )^2 )

    = ( (256 + 144 ) = ( 400 )= 20

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( 16 + 9 )^2 + ( 7 - 7 ) ^2 ) = ( 25 )^2 ) = (625 ) = 25

    = 15 + 20 + 25 = 60

    :-

    ( - 3 , 4 ) , ( 2 , 16 ) , ( 8 , 6 ) , ( 0 , 0 )

    .

    :-

    =

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( 2 + 3 )^2 + ( 16 - 4 )^2 ) = ( 169) = 13

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( (6 )^2 + ( - 10 )^2 = ( 136 ) = 11.662

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( - 6 ) ^2 + ( - 8 )^2 ) = ( 100 ) = 10

    = ( ( 2 - 1 ) ^2 + ( 2 - 1 )^2 )

    = ( ( 3 )^2 + ( - 4 ) ^2 ) = ( 25 ) = 5

    = 10 + 5 + 13 + 11.662 = 39.7

    :-

    ( 1 , 1 ) , ( 2 , 3 )



    :-

    = { ( 2 - 1 )^2 + ( 2 - 1 )^2 }

    = { ( 2 - 1 )^2 + ( 3 - 1 )^2 }

    = ( 1 + 4 ) = 2.24

    __________________


    :-

    ( 0 , 0 ) , ( - 3 , 4 )

    :-

    = ( ( 2 - 1 )^2 + ( 2 - 1 )^2 )

    = ( - 3 ) ^2 + ( 4 )^2 )

    = 5















  2. #2
      Eiman
    Jul 2011
    -
    14,750

    : 1

    .......

  3. #3

    Feb 2014
    30


: 1 (0 1 )